AKAD MUAMALAH DI PASAR MODAL SYARIAH - Ali Amin Isfandiar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
Shifting paradigm on capital market from conventional to shariah one supports to change the instrument usage. Because of prohibited status on debt trading (obligation or sukuk), interest instrument which has been used in capital market should be modified. Therefore ‘aqd muamalah is choosen and implemented to legalize debt contract on capital market. Ijarah and mudharabah has been implemented to shariah capital market. Beside both, it uses ‘aqd murabahah as contract instrument. Up to now, National Shariah Board (Dewan Shariah Nasional) was issued two fatawas on both of the first namely Fatwa DSN No.33/DSN-MUI/IX/2002 on shariah obligation based on mudharabah contract and Fatwa DSN No.41/DSN-MUI/III/2004 on shariah obligation on ijarah contract, beside the other fatwa on shariah obligation itself, Fatwa DSN No.32/DSN-MUI/IX/2002 deals with the shariah obligation. By fatawas, legalization of shariah obligation was actually guaranteed as to be implemented on shariah capital market and it can be seen to product variation published by financial institution.